Correlating cardiotocography, apgar score and cord blood ph after caesarean section for fetal distress at Rahima Moosa mother and child hospital - Ashley, Tshikanda Khathutshelo (My University, 2018)
Background Fetal distress is one of the most common indications for emergency caesarean section in both developed and developing countries. Intrapartum fetal monitoring was designed with the hope of reducing the prevalence of cerebral palsy and early detection of fetal hypoxia. The most commonly used method of intrapartum fetal surveillance is cardiotocography (CTG). The use of umbilical cord artery blood gases can provide important information about the acid-base status of the newborn. The aim of this study was to correlate intrapartum CTG findings with the outcome of the newborns in terms of umbilical cord pH and Apgar scores, in women who underwent caesarean sections for fetal distress at term and were in labour, and thus to evaluate the accuracy of CTGs. Methods This study included 99 women with term singleton pregnancies, who were in labour and underwent caesarean section for fetal distress. CTG tracings were interpreted by a senior obstetrician as normal, non-reassuring or abnormal. The senior obstetrician interpreted these CTGs without knowledge of the acid-base statuses of the newborns. Umbilical artery blood was taken immediately after birth in a heparinized syringe and was analysed in less than 30 minutes. A pH of < 7.1 was taken as acidosis and a pH of ≥7.1 was taken as normal. Results The age range was 18-46 years. The number of women with gestational age of 42 weeks or more was 8 (8%). The interval between end of CTG and birth ranged from 21 to 352 minutes. Three women had a hypertensive disorder and none had diabetes mellitus. The birth weight range was 2125-4240 g. The median Apgar score at 1 minute was 9 (range 1-9), and at 5 minutes was 10 (range 7-10). No infants required admission to the neonatal intensive care unit, none developed hypoxic-ischaemic encephalopathy, and none died. The CTG interpretation found 9 normal, 21 non-reasuring and 69 abnormal tracings.The cord blood pH correlated well with the lactate level (r=-0.82; p<0.001), and also with the base deficit (r=-0.78; p<0.001). The Apgar scores at 1 minute and 5 minutes also correlated well with the pH (both r=0.44 with p<0.001). When the Apgar score at 5 minutes was <9 (n=7), mean pH was 7.04, and when it was ≥9, the mean pH was 7.22 (p<0.001). Following fetal distress in the latent phase of labour, the mean pH was 7.23, while after the active phase of labour, the mean pH was 7.1 (p=0.017). Normal, non-reassuring and abnormal fetal heart rate (FHR) patterns were followed by cord blood pH values of 7.19, 7.21 and 7.21 respectively p=0.879). Conclusion: The predictive value of CTGs for neonatal encephalopathy was zero in this series, although the sample size of was small, given the rarity of neonatal encephalopathy. The neonatal outcome may however have been modified (improved) by the performance of caesarean section. There was a good correlation between Apgar scores and cord blood pH. Within this group of 99 infants delivered for suspected fetal distress, different fetal heart rate patterns could not be related to neonatal outcome. The study confirms the low predictive value of CTG tracings in the diagnosis of neonatal acidaemia and prediction of poor neonatal outcome, but cannot exclude the possibility that a proportion of infants may have benefited from caesarean section following CTG monitoring.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science, Johannesburg, 2017
Keywords: Cardiotocography (CTG); Fetal Distress; Respiratory Distress Syndrome, Newborn; Cesarean Section